αβ/γδ T cell lineage outcome is regulated by intrathymic cell localization and environmental signals - Aghaallaei, Nargessadat; Dick, Advaita M.; Tsingos, Erika; Inoue, Daigo; Hasel, Eva Mareike; Thumberger, Thomas; Toyoda, Atsushi; Leptin, Maria; Wittbrodt, Joachim; Bajoghli, Baubak (Science advances, 2021)
αβ and γδ T cells are two distinct sublineages that develop in the vertebrate thymus. Thus far, their differentiation from a common progenitor is mostly understood to be regulated by intrinsic mechanisms. However, the proportion of αβ/γδ T cells varies in different vertebrate taxa. How this process is regulated in species that tend to produce a high frequency of γδ T cells is unstudied. Using an in vivo teleost model, the medaka, we report that progenitors first enter a thymic niche where their development into γδ T cells is favored. Translocation from this niche, mediated by chemokine receptor Ccr9b, is a prerequisite for their differentiation into αβ T cells. On the other hand, the thymic niche also generates opposing gradients of the cytokine interleukin-7 and chemokine Ccl25a, and, together, they influence the lineage outcome. We propose a previously unknown mechanism that determines the proportion of αβ/γδ lineages within species. - The level of γδ T cells varies between species because of differences in cellular dynamics and signals from thymic niche. - The level of γδ T cells varies between species because of differences in cellular dynamics and signals from thymic niche.
Gesehen am 27.07.2021